PENGARUH LOKASI TEMPAT TINGGAL DAN ADVERSITY QUOTIENT TERHADAP ADAPTASI PADA PERMUKIMAN - Deni Kurniawan (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2016)
The research objectivewas to obtain empirical data on the effect of location of residence and adversity quotient to adaptation on settlements. The Ex Post Facto research using dependent variable: adaptation to settlement, independent variables: location of residence, while the independent variable attributes: low and high adversity quotient. The results showed the first hypothesis, third, and fourth that the location of residence has an influence on adaptation to settlement. The receipt of significance evidences this, there are differences in adaptation to the location of settlements in both same results were also evidenced in the different test group svariance between two locations on adversity quotient group. But on the second hypothesis, there has been no significant interaction between location of residence and adversity quotient to adaptation on settlements, as evidenced receipt of H0, this hypothesis cannot be verified based on the results of processing the data collected under the various possibilities that occurin decision hypothesis formulation, process research,and other factors.